The Importance of Usability Aspect in M-Commerce Application for Satisfaction and Continuance Intention - Yassierli, Yassierli; Vinsensius, Vinsensius; Mohamed, M. S. Syed (Makara Journal of Technology, 2018)
There has been a rapid growing of m-commerce application in recent years due to the development of mobile communication technology and e-commerce business. However, only about 30% of online users, who conduct online searching, make online purchases. The low conversion rate seems to be correlated with poor usability aspect of most m-commerce applications and poor satisfaction reported by users. Research has reported that satisfaction and continuance intention in using m-commerce applications have relationships with service quality and information quality. In this study, a new model of user satisfaction and continuance intention in the context of mobile application was proposed by incorporating usability aspect. The study involved 230 respondents. To develop a new reliable and valid model, this study used Structural Equation Modelling (SEM) that include two stage evaluation, namely measurement model evaluation and structural model evaluation. Results demonstrated 34 valid and reliable indicators which can be used to measure service quality, information quality, usability, user satisfaction and continuance intention in M-commerce application. There were positive and significant relationships among service quality, information quality, usability, user satisfaction, and continuance intention. This study provide evidence on the importance of usability aspect in M-commerce application for user satisfaction and continuance intention.